Diversidad del frijol en Mexico y actividades de recoleccion de germoplasma - Debouck, Daniel G. (International Center for Tropical Agriculture, 1978)
The formation of centers of genetic diversity of Phaseolus spp. in different parts of the world is discussed. Botanical, archeological and ethnobotanical arguments are given to support the statement that the primary center of origin was in the Americas, with 2 subcenters or centers of diversity (Mesoamerica and Peru). As expected, genetic erosion linked with changes in agriculture was found almost everywhere. Priorities include the collection of native P. vulgaris var., as well as the 4 other cultivated spp., native or modern var. from special agro-ecological zones, ancestral forms or wild regressions of cultivated spp., and exclusive world spp. Problems in collecting and details of collecting activities in 1978-79 are reported. (CIAT)